2022
DOI: 10.32743/unitech.2022.98.5.13641
|View full text |Cite
|
Sign up to set email alerts
|

To the Energy of Non - Electrifed Sections of Railways

Abstract: Выходные данные статьи и справка о публикации: в день оплаты статьи Рассылка печатных журналов и оттисков: 05.09.2022

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To solve the problems of transportation work of locomotives, it is necessary to find a solution to equation (2), which determines the results of calculating all the coordinates of the object under study.…”
Section: Objects and Methods Of Researchmentioning
confidence: 99%
“…To solve the problems of transportation work of locomotives, it is necessary to find a solution to equation (2), which determines the results of calculating all the coordinates of the object under study.…”
Section: Objects and Methods Of Researchmentioning
confidence: 99%
“…The characteristic of the studied virtual section of the railway are given in table. 1, and the design and traction-energy parameters of the UzTE16M3 freight diesel locomotive under study are indicated in [22,23]. As a result of the interaction of the locomotive and cars along the route, movements and vibrations (oscillations) of the rolling stock and its parts of different magnitude in all directions arise, namely: longitudinal, transverse and vertical, as well as rotations relative of to the vertical and horizontal axes.…”
Section: Objects and Methods Of Researchmentioning
confidence: 99%